EKSPLORASI PENALARAN SISWA DALAM PEMBELAJARAN MENGGUNAKAN SOAL BERKONSEP PMRI TENTANG ARITMATIKA SOSIAL DI SMP - Nabila Putri Isamer; Zulkardi _; Ratu Ilma; Ely Susanti (Universitas Muhammadiyah Semarang, 2022)
This article aims to examine the reasoning of students in the mathematical study of social arithmetic that focuses on profit or loss. The study is a descriptive study using pmri (Indonesia's realistic math education) that starts with online shopping as a context for both early learning and for profit or loss at the end of learning. The subject of this study is class VII SMP at lubuklinggau. Research shows that the problem with context can help students identify important information on matters about the concept of social arithmetic. The use of context in questions provides reasoning and understanding of the mathematical concepts learned.